Proceedings of the 5th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2019) 2020
DOI: 10.2991/assehr.k.200120.056
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective of Husband and Wife Roles in Long-Distance Marriage

Abstract: Marriage aims not only to obtain social acceptance but also to have a long-lasting companionship. Longdistance marriage is a relationship between husband and wife that is both legally and religiously bound. In this research, three samples are used: one sample is an employee, one sample is a lecturer, and one other sample is a university student. In more detail, the samples are: N (26) with a husband working in Cikarang, P (28) is an employee whose husband working in Makassar, and R (35) is a university studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…The study found that individuals who live separately from their partners tend to have a higher level of marital distress than individuals who live with their partners. The inability of one partner to optimally perform their role and the many obstacles that exist make long-distance relationships can be complicated for many couples [26].…”
Section: Icopsymentioning
confidence: 99%
“…The study found that individuals who live separately from their partners tend to have a higher level of marital distress than individuals who live with their partners. The inability of one partner to optimally perform their role and the many obstacles that exist make long-distance relationships can be complicated for many couples [26].…”
Section: Icopsymentioning
confidence: 99%
“…The distance that separates them reduces the frequency of meetings and face-toface communication (Rubyasih, 2016). According to Harsari (2020), wives with LDM status experience difficult times, especially in maintaining communication. In fact, communication is one of the foundations for creating harmony in marriage which obtained through interpersonal relationships between husband and wife (Dewi & Sudhana, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explained that long-distance marriages have a number of risks since partners are unable to make physical contact and sometimes lack communication (Amana et al, 2020) which is marked by difficulty in communicating, experiencing quarrels, and loneliness (Harsari, 2020). On the other side, to maintain a long-distance marriage, couples often rely on technology, such as video calls through social media.…”
Section: Introductionmentioning
confidence: 99%
“…Health indicators such as stress levels in women who undergo long-distance marriage tend to be higher than men (Anand et al, 2018) so that the wife's condition has more psychological vulnerabilities in undergoing long-distance marriages. There is another study, where it stated that wives will experience loneliness and feel the absence of husbands in caring for children (Harsari, 2020). A couple have material and sexual needs that can arise at any time and will certainly be difficult to fulfill if they are in a long-distance relationship.…”
Section: Introductionmentioning
confidence: 99%